2017
DOI: 10.1038/s41598-017-01506-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation in Plasmodium falciparum Histidine Rich Proteins 2 and 3 in Indian isolates: Implications for Malaria Rapid Diagnostic Test Performance

Abstract: Commercial malaria rapid diagnostic tests (RDTs) detect P. falciparum histidine rich protein 2 (PfHRP2) and cross react with PfHRP3, a structural homologue. Here, we analysed natural variations in PfHRP2 and PfHRP3 sequences from Indian isolates and correlated these variations with RDT reactivity. A total 1392 P. falciparum positive samples collected from eight endemic states were PCR amplified for Pfhrp2 and Pfhrp3 genes and were sequenced. The deduced protein sequences were analysed for repeat variations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 18 publications
4
34
1
Order By: Relevance
“…Thus, the genetic variation in pfhrp2 does not appear to affect RDT detection sensitivity at ³ 200 parasites/μL. 9 Consistent with Baker et al's subsequent conclusion, similar results have been reported by Kumar Bharti et al 11 using P. falciparum-positive blood samples collected from 15 sites in eight malaria-endemic states in India and by Willie et al 12 using samples collected from three health centers in the Ampasimpotsy area in Madagascar.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Thus, the genetic variation in pfhrp2 does not appear to affect RDT detection sensitivity at ³ 200 parasites/μL. 9 Consistent with Baker et al's subsequent conclusion, similar results have been reported by Kumar Bharti et al 11 using P. falciparum-positive blood samples collected from 15 sites in eight malaria-endemic states in India and by Willie et al 12 using samples collected from three health centers in the Ampasimpotsy area in Madagascar.…”
Section: Introductionsupporting
confidence: 77%
“…9,10 Detection sensitivity for different RDTs tested in different populations in PNG was as low as 45.6% 7 to as high as 96%. 6 Although the correlation between RDT performance and pfhrp2 variation remains unclear, [9][10][11][12] the studies that have tested RDTs in PNG did not analyze pfhrp2 variation. [3][4][5][6][7] All 18 sequences in the present study were generated from 12 samples that were P. falciparum positive by LDR-FMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the prevalence of deletion is calculated taking account the number of Pf detected by SnM-PCR (763) the frequencies for each case were: deletion in both genes, 10…”
Section: Resultsmentioning
confidence: 99%